Herpetic involvement of larynx presenting as a supraglottic mass - Ali Cemal Yumuşakhuylu; Murat Sarı; Zahide Mine Yazıcı; Alper Tutkun; Süheyla Bozkurt Uyar (Turkish Archives of Otorhinolaryngology, 2010)

(untitled)
The goal of this paper is to report an interesting case of laryngeal involvement by herpes virus, showing a clinical aspect very alike to an extense neoplasm of this region. We describe a case of supraglottic mass caused by Herpes simplex virus in an immune-competent adult in which the correct diagnosis was not suspected at the first examination. At first we suspected laryngeal malignancy. A biopsy specimen revealed exact diagnosis. Early suspicion and proper evaluation are mandatory to prevent a life-threatening crisis and false surgery technique. Supraglottitis due to Herpes simplex virus is especially rare entity with few reported cases in literature. True incidence of herpetic infections of the larynx is unknown. Accurate diagnosis requires clinical suspicion and highly specific method of confirming the presence of the virus.